Aloe immaculata and A. affinis (Asphodelaceae subfam. Alooideae), two endemics from northern and eastern South Africa, are different maculate aloe species - Smith, Gideon F.; Klopper, Ronell R. (Phytotaxa, 2022)
We show that Aloe immaculata and A. affinis (Asphodelaceae subfam. Alooideae) are two different species. Aloe immaculata, a Limpopo province, South Africa, endemic, is therefore reinstated and treated as distinct from A. affinis, an endemic of the eastern, mainly Drakensberg escarpment in Mpumalanga, South Africa, and southeastern Limpopo, and northwestern Eswatini. Vegetatively, the two species mainly differ in terms of leaf colour (dull green to brownish green in the case of A. immaculata and brighter green in the case of A. affinis). Reproductively, the species differ in inflorescence structure (subcapitate to conical and round-topped racemes in the case of A. immaculata and cylindric-acuminate ones in the case of A. affinis) and flower size and colour (pale flesh pink and 28–33 mm long in A. immaculata and scarlet red and 40–45 mm long in A. affinis). The two species are compared and illustrated, and descriptions for both species and a combined distribution map are provided.